Medical School Accreditation Factors Associated With Certification by the Educational Commission for Foreign Medical Graduates (ECFMG): A 10-Year International Study. (September 2021) - Tackett, Sean; Boulet, John R.; van Zanten, Marta
Abstract : Purpose: In 2024, international medical graduates seeking Educational Commission for Foreign Medical Graduates (ECFMG) certification will be required to graduate from an accredited medical school. This study's goal was to examine relationships between medical school accreditation variables and ECFMG certification for a global sample. Method: Using ECFMG databases, the authors created a 10-year cohort (January 1, 2007–December 31, 2016) of certification applicants, defined as individuals who had attempted at least 2 examinations required for certification. The authors aggregated applicant data at the school level, excluding schools with < 80 applicants. School accreditation statuses were based on agency websites. School region, age, and time of first accreditation were included. Analyses included descriptive and bivariate statistics and multiple linear regressions adjusting for school start year and year of first accreditation. Results: The cohort included 128, 046 applicants from 1, 973 medical schools across 162 countries. After excluding low-volume schools, 318 schools across 81 countries remained. These provided 99, 598 applicants and 77, 919 certificate holders, three-quarters of whom came from the Caribbean, South-Central Asia, and West Asia regions. Two hundred and fifty (78.6%) schools were accredited; 68 (21.4%) were not. Most ECFMG applicants (n = 84, 776, 85.1%) and certificate holders (n = 68, 444, 87.8%) attended accredited medical schools. Accredited schools had higher rates of ECFMG certification among graduates than nonaccredited schools in comparisons that included all schools (75.0% [standard deviation (SD) = 10.6%] vs 68.3% (SD = 15.9%), P < .001), and for countries that had both accredited and nonaccredited schools (73.9% [SD = 11.4%] vs 67.3% [SD = 16.8%], P = .023). After adjusting for age of school, longer duration of accreditation was associated with higher certification rates ( P < .001). Conclusions: Accreditation had a positive association with ECFMG certification rates. Future studies should investigate how accreditation processes might account for higher certification rates. Abstract : Supplemental Digital Content is available in the text.